Deformation and fracture mechanics of WC-(Fe-Mn-C) composite in axial compression - Sevostyanova, Irina N.; Sablina, Tatiana Yu; Burlachenko, A. G.; Kulkov, Sergey N. (Physical Mesomechanics)
The paper analyzes the surface relief of a tungsten carbide-ferromanganese steel composite (WC-(Fe-Mn-C)) under axial compression, including its structure on the microscale (variation in coherent scattering region sizes and mode II stresses) and on the macroscale (accumulation of deformed WC grains and interface cracks, evolution of ordered shear bands). The analysis shows that compressing the composite decreases the average size of plastically deformed WC grains, increases the density of interface microcracks, and decreases the average shear band spacing. The composite reveals a stage character of deformation and prefracture correlating with its stress-strain curve. In the first strain hardening stage, the material is deformed in its matrix and WC grains without continuity loss. In the second stage, numerous shear macrobands oriented in two directions at similar to 45 degrees to the loading axis appear on its free surfaces. The macrobands are rich in deformed grains and cracks. Their intersection gives rise to macrocracks of length 40-150 mu m as precursors of catastrophic failure. Also presented are X-ray diffraction data on the fine crystal structure of the carbide and binder phases of WC-(Fe-Mn-C) at different loading stages. The data suggests that increasing the strain decreases the size of coherent scattering regions and increases the lattice microstress in both phases. The binder starts to deform earlier than the tungsten carbide. Most of the change in the fine crystal structure of the tungsten carbide falls on the stage of shear band formation.